Description of Mother's Knowledge About Handling Diarrhea in Toddlers (JURNAL IBU DAN ANAK, 2022)
Diarrhea is still a public health problem in developing countries such as Indonesia, because of its high morbidity and mortality. The morbidity survey conducted by the diarrhea sub-directorate of the Ministry of Health from 2010 seems to have a tendency to increase in incidence.Aim of this research is to describe Mother's Knowledge About Handling Diarrhea in Toddlers at Baamang II Public Health Center. This type of research uses a descriptive method with a cross sectional design with a sample of 30 people using primary data with accidental sampling technique. The single variable is Mother's Knowledge About Handling Diarrhea in Toddlers. Result of research From 30 respondents there were 11 respondents (36.7%) with good knowledge, 14 respondents (46.7%) with sufficient knowledge and as many as 5 people (16.0%) with less knowledge.